Study of Insect Diversity in Rice Agroecosystem in Karawang West Java - Siriyah, Siti Latifatus; Khamid, Miftakhul B.R.; Bayfurqon, Fawzy M (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2018)
Insects were collected from rice fields in Karawang West Java. Since insects are dominant in Rice field, their role in the ecosystem are important regarding the rice production. Therefore, the occurance of insect species and their role in ecosystem are important to understand. The aim of this reasearch was to study the insect occurance in rice field in Karawang to obtain the potential candidate for biological control agent. The insects were collected using sweep net, pit fall trap and light trap. Nine insect orders were collected and 49 morphospecies were identified including insect pest, parasitoids, predator, tourist and detritivore. Paederus sp., Cyrtohinus and Micraspis sp., were the most abundant entomophagous insect that is potential candidate for biological control agent in Karawang. Keywords: insect, insect diversity, rice fields, karawang